Frequency of Hepatitis a Virus as a Cause of Anicteric Hepatitis in Children Under 5 Years - Irfan Khan, Irfan Ullah, Saeedullah, Zahid Irfan Marwat, Arshad Khan, Hamayun Anwar (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Globally, Acute viral hepatitis A is the widespread type of hepatitis particularly in developing countries. Children under 5 year of age are at greater risk of asymptomatic infections, and if they do develop symptoms, they are likely to experience anicteric illnesses. The present study aimed to determine the incidence of hepatitis A virus as anicteric hepatitis cause among children under 5 years. Methodology: A cross-sectional study was carried out on 380 children (<5 years) in the Pediatric Medicine Department of Qazi Hussain Ahmad Medical Complex Nowshera for the duration from 1st July 2021 to 30th June 2022. Study protocol was approved by the institute ethical committee. Children with normal-colored urine, diarrhea, abdominal pain, vomiting, malaise, nausea, and low-grade fever (< 38.5 °C) were investigated. Demographic details and physical examination were recorded from children with elevated transaminase levels (ALT). Children with elevated transaminases were only enrolled and categorized into two groups: Group-I HAV-positive and Group-II HAV negative groups. Children with transaminases were the only ones who had IgM antibodies against HAV virus. ELISA was used to test for anti-HAV IgM. Results: Of the total 380 children, the incidence of elevated transaminases (ALT, AST) were 42.6% (n=162). The frequency of HAV positive and HAV negative was 13.6% (n=22) and 86.4% (n=140) respectively. Out of 162 children, there 84 (51.9%) male and 78 (48.1%) females. Age-wise distribution of patients were as follows: Age≥3 years 92 (56.8%) and age≤ 70 (43.2%). HAV infection rates were significantly higher among children over 2 years old (p <0.05). Abdominal pain, vomiting, diarrhea, nausea, Right hypochondrial tenderness, Arthralgia, and Hepatomegaly were different clinical manifestation of HAV negative and HAV positive found in 20.7% (n=29) versus 13.6% (n=3), 97.1% (n=136) versus 81.8% (n=18), 87.1% (n=122) vs 81.8% (n=18), 81.4% (n=114) versus 95.5% (n=21), 32.9% (n=46) versus 86.4% (n=19), 38.6% (n=54) versus 59.1% (n=13), 4.3% (n=6) versus 18.2% (n=4) respectively. Conclusion: Children with anicteric hepatitis under the age of 5 years were found to have 13.6% HAV infection. Diarrhea and vomiting were the most prevalent clinical manifestation of children < 5 years. A higher level of maternal education, older age, and poor sanitary conditions were various risk factors related to HAV infection. Keywords: Hepatitis A, Anicteric hepatitis, Children